Endothelial characteristics in healthy endothelial colony forming cells; generating a robust and valid ex vivo model for vascular disease. (18th August 2020) - de Boer, Suzan; Bowman, Mackenzie; Notley, Colleen; Mo, Aomei; Lima, Patricia; de Jong, Annika; Dirven, Richard; Weijers, Ester; Lillicrap, David; James, Paula; Eikenboom, Jeroen
Abstract: Background: Endothelial colony forming cells (ECFCs) derived from peripheral blood can be used to analyze the pathophysiology of vascular diseases ex vivo. However, heterogeneity is observed between ECFC clones and this variability needs to be understood and standardized for ECFCs to be used as a cell model for applications in vascular studies. Objective: Determine reference characteristics of healthy control ECFCs to generate a valid ex vivo model for vascular disease. Methods: Putative ECFCs (n = 47) derived from 21 individual healthy subjects were studied for cell morphology and specific cell characteristics. Clones were analyzed for the production and secretion of von Willebrand factor (VWF), cell proliferation, and the expression of endothelial cell markers. Results: Based on morphology, clones were categorized into three groups. Group 1 consisted of clones with classic endothelial cell morphology, whereas groups 2 and 3 contained less condensed cells with increasing cell sizes. All clones had comparable endothelial cell surface expression profiles, with low levels of non‐endothelial markers. However, a decrease in CD31 and a group‐related increase in CD309 and CD45 expression, combined with a decrease in cell proliferation and VWF production and secretion, was observed in clones in group 3 and to a lesser extent in group 2. Conclusions: We observed group‐related variations in endothelial cell characteristics when clones lacked the classic endothelial cell morphology. Despite this variation, clones in all groups expressed endothelial cell surface markers. Provided that clones with similar characteristics are compared, we believe ECFCs are a valid ex vivo model to study vascular disease.